PENGEMBANGAN BAHAN AJAR DIGITAL TEKS CERITA RAKYAT KELAS X BERTEMA KEJADIAN SEJARAH DAERAH ASAL - Eldiana, Sheilla; Kartikasari, Ratna Dewi (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This study aims to develop digital teaching materials for class X folklore texts with the theme of Regional Historical Events of Origin, as well as to determine the feasibility of digital teaching materials and students' responses to digital teaching materials. The development model used in this study is the Borg and Gall development model with eight simplified stages, namely 1) problem identification and data collection, 2) initial product design, 3) design validation, 4) design revision, 5) initial trial , 6) initial product revision, 7) usage trial, and 8) final product revision. Interview techniques and questionnaires were used to collect data with subject matter experts, media experts, class X students at SMAN 3 Kota Tangerang, and Indonesian teachers. The research results obtained were: 1) subject matter expert validation obtained 98% in the very feasible category, 2) media expert validation obtained 90% in the very feasible category, 3) Indonesian language teachers obtained 95%, and 4) Response of class X students of SMAN 3 Tangerang City gets 91% with very decent category. Based on the data from the assessment results, it was concluded that the digital teaching material for class X folktale texts is very suitable for use in learning at school.